A review on oxidation of elemental mercury from coal-fired flue gas with selective catalytic reduction catalysts. Issue 7 (22nd July 2015) - Zhao, Lingkui; Li, Caiting; Zhang, Xunan; Zeng, Guangming; Zhang, Jie; Xie, Yin'e
<x xml:space="preserve">Abstract</x> Transformation and speciation of Hg in coal-fired flue gas, mechanism and kinetics for oxidizing Hg0 with SCR catalysts were discussed.